Electrochemical Behavior of UO2F2 and Its Electrodeposition from UO2F2-FLiNaK Melt. Issue 7 (1st January 2018) - Han, Dong; She, ChangFeng; Peng, Jia; Jiang, Feng; Yang, Xu; Peng, Hao; Yang, Yang; Zheng, Haiyang; Wang, Xianbin; Xu, Qianhui; Wang, Chenyang; Zhu, Tiejian; et al.
Abstract : The electrochemical behavior of UO2 F2 in LiF-NaF-KF (46.5-11.5-42 mol%, FLiNaK) melt on Pt electrode was investigated at 550°C by cyclic voltammetry (CV) and square wave voltammetry (SWV). UO2 F2 was prepared by the reaction of UF4 powder and oxygen at 650°C, and ascertained by X-ray diffraction (XRD) and Raman spectroscopy. It was found that the reduction of UO2 2+ in FLiNaK exhibited two steps both with one exchanged electron: UO2 2+ + e − → UO2 + and UO2 + + e − → UO2, with the CV reduction peak at about 2.02 V and 1.49 V (vs. K + /K), respectively. Both of them were reversible and diffusion-controlled. By means of potentiostatic electrolysis, the product of UO2 was obtained and the separation ratio of uranium from UO2 F2 -FLiNaK melt was approximately 54.5% at 550°C, which were characterized by XRD and the inductively coupled plasma atomic emission spectrometer (ICP-AES).